Selective serotonin reuptake inhibitor induced bleeding disorder in neurosurgical patients ‐ a cause for concern ?. Issue 2 (21st July 2016) - Zahavi, Guy; Berkenstadt, Haim; Ben‐Menahem, Erez; Cohen, Zvi; Lubetsky, Aaron; Nahtomi‐Shick, Orit
Summary: Normal haemostasis is imperative during neurosurgery. We report a case of a neurosurgical patient with normal routine laboratory investigations but a history suggestive of an increased bleeding risk associated with a selective serotonin reuptake inhibitor (SSRI). Current evidence suggests there is a link between the use of SSRIs and peri‐operative bleeding and that discontinuation of these drugs should be considered in patients at high risk, such as in the context of neurosurgery.